(Re)composing: A study of the musical documentary in reimagining the historical archive through song - Roberts, Daniel Ronald Newland (University of the Witwatersrand, Johannesburg, 2023)
This thesis investigates conventional documentary reenactments and proposes a different approach by examining the role of purpose-composed songs as a medium for historical reenactment in the music documentary. It scrutinizes this approach as an alternative to traditional notions of reenactment often associated with Hollywood-style documentaries where the convention is to restage historical events. Instead, the argument made is for the transformative and imaginative of poetic verse and musical expression to embody historical texts. The research explores the profound connection between the performer and the historical subjects through ancestral bonds, examining how this relationship enhances the performance's potency. In addition, it delves into the collaborative process between musicians and documentarians in creating purpose-composed songs, especially when performances are situated within locations deeply connected to the historical context, assessing how this impacts audience engagement. Reflecting on the evolution of the music documentary genre since the 1960s, the thesis critically examines Bill Nichols’s enduring analysis of documentary modes. It investigates the continued reliance on the vérité style in music documentaries while using selected case studies to map more diverse documentary forms extending beyond Nichols's purely observational mode. The artistic component of this research is an essay film, which offers a contemplative view of the symbiotic relationship between cinematographer and musician. It probes into the nuances of creating poignant artistic expressions that address historical traumas while simultaneously managing the complex interplay of the subjectivities inherent in filmmaker and musician. This dual-focused inquiry seeks to illuminate the capacity of music documentaries to convey historical narratives in a manner that resonates with contemporary audiences, marrying historical accuracy with emotional depth.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Arts, Film and Television to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Purpose-composed songs; Reenactments; Cinéma vérité; Music documentary; Bill Nichols; SDG-11: Sustainable cities and communities